ANALISIS HAMBATAN GURU DALAM MENERAPKAN KURIKULUM MERDEKA PADA MATA PELAJARAN IPAS KELAS IV SD NEGERI III GENTENG WETAN - Hidriyani, Fudna; Ramiati, Eka; Ihsan, Moh.Hayatul (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2024)
This study aimed to explain the analysis of teachers' obstacles in implementing the independent curriculum in the science and science subjects of grade IV of SD Negeri III Genteng Wetan. This study used a qualitative approach of the case study type. The subjects in this study were the principal and teacher of grade IV of SD Negeri III Genteng Wetan. In the process of collecting data, several methods were used, namely observation, interviews, and documentation. Data analysis techniques used data collection, data reduction, data presentation, and conclusion drawn. The results of this study were that at the learning planning stage, teachers experienced obstacles in compiling learning tools independently. Starting from analyzing CP, formulating TP, compiling ATP, and designing and developing teaching modules along with KKTP. Furthermore, at the stage of implementing learning, the obstacles for teachers lay in the core activities that they had not used varied learning methods, faced difficulties in using technology, had not implemented differentiated learning, and had not fully understood the concept of the Pancasila Student Profile Strengthening Project (P5). The obstacles for teachers in learning evaluation were related to diagnostic assessments that should have been carried out at the beginning of the school year to understand the conditions and characteristics of students. Of the various obstacles of teachers, this was due to the limited ability of teachers in terms of using technology and understanding the concept or learning model in the independent curriculum due to the age factor.